2019
DOI: 10.3390/atmos10010038
|View full text |Cite
|
Sign up to set email alerts
|

A Turbulence-Oriented Approach to Retrieve Various Atmospheric Parameters Using Advanced Lidar Data Processing Techniques

Abstract: The article is aimed at presenting a semi-empirical model coded and computed in the programming language Python, which utilizes data gathered with a standard biaxial elastic lidar platform in order to calculate the altitude profiles of the structure coefficients of the atmospheric refraction index C N 2 ( z ) and other associated turbulence parameters. Additionally, the model can be used to calculate the PBL (Planetary Boundary Layer) height, and other parameters typically employed in the field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…High EC episodes occurred around 22.1% and 21.4% at the Ias , i and Cluj-Napoca, respectively. Reported case studies have shown that the presence of fine particles type is specific for the spring and winter seasons [25,30,40,41,43,44]. In contrast, for Bucharest, the EC dominated occurred with a presence of up to 13.3%.…”
Section: Dust Occurrence Over Romania From Aeronet-actris-ro Observatmentioning
confidence: 99%
“…High EC episodes occurred around 22.1% and 21.4% at the Ias , i and Cluj-Napoca, respectively. Reported case studies have shown that the presence of fine particles type is specific for the spring and winter seasons [25,30,40,41,43,44]. In contrast, for Bucharest, the EC dominated occurred with a presence of up to 13.3%.…”
Section: Dust Occurrence Over Romania From Aeronet-actris-ro Observatmentioning
confidence: 99%
“…Therefore, in this paper, our main intention is to provide more information through multi-source data integration. In Romania there are several studies focusing on Saharan dust intrusions [28][29][30][31]. However, these studies were conducted in the southern and eastern part of Romania.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of weather conditions with specific localized impacts on vertical mixing need to be investigated [5]. In comparison to air-based in situ measurements, high temporal and spatial resolution LiDAR measurements has proven to be very useful for identifying aerosol sources and transport mechanisms as well as the evolution of the PBL [6][7][8][9][10]. Although satellite-based global observation tools [11][12][13][14] could in principle be used, these measurements have considerable uncertainty and are available only in limited time slots, as satellites have typical revisit times of two weeks.…”
Section: Introductionmentioning
confidence: 99%